1987
DOI: 10.1177/105381518701200104
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Academic Responding of Handicapped Preschool Children During Group Instruction

Abstract: In an experimental assessment of a choral responding procedure for increasing children's response to teacher commands, decreased levels of off-task behavior, as well as increased levels of correct responding, resulted from the procedures for three handicapped preschool children during large group instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…The purpose of using OTR is to increase the number of active child responses, which in turn increases correct responses and engagement (Heward, 1994). Research literature indicates a positive relationship between increased rates of OTR and on-task behavior, correct responses, and fewer disruptive behaviors of students (Carnine, 1976;Sainato, Strain, & Lyon, 1987;. Additionally, research suggests that the disruptive behavior of students with EBD covaries with both correct responses and active responding (Sutherland & Snyder, 2007a, 2007b.…”
Section: Model Componentsmentioning
confidence: 89%
“…The purpose of using OTR is to increase the number of active child responses, which in turn increases correct responses and engagement (Heward, 1994). Research literature indicates a positive relationship between increased rates of OTR and on-task behavior, correct responses, and fewer disruptive behaviors of students (Carnine, 1976;Sainato, Strain, & Lyon, 1987;. Additionally, research suggests that the disruptive behavior of students with EBD covaries with both correct responses and active responding (Sutherland & Snyder, 2007a, 2007b.…”
Section: Model Componentsmentioning
confidence: 89%
“…Providing students frequent opportunities to respond is important because researchers suggest that increased student responding is linked to on-task behavior and engagement during instruction (Carnine, 1976;Sainato et al, 1987;Sutherland et al, 2003). When students are engaged and actively responding to questions, teachers can focus on academic content rather than being concerned with inappropriate student behaviors.…”
mentioning
confidence: 98%
“…Sainato et al (1987) compared choral responding with a baseline individual responding condition with three preschool children identified as having significant behavioral and developmental delays during morning circle time. Sainato and colleagues compared the use of two rates (three/min; five/min) of choral responding with a baseline individual responding condition and results indicated that on-task behavior and correct responding improved during the higher rate of choral responding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sainato, Strain, and Lyon (1987) increased academic responding of preschool children with disabilities during group instruction. Similarly, Rule and her colleagues (1990) were able to teach school survival skills to children within the preschool environment.…”
mentioning
confidence: 93%